2021
DOI: 10.1177/15589250211020311
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of strain-hardening cementitious composite to curing conditions as a retrofitting material for RC beams

Abstract: Strain-hardening cement-based composites (SHCC) have recently been developed as repair materials for the improvement of crack control and strength of flexural members. This work focuses on strengthening and flexural enhancement using SHCC layer in tensile regions of flexural members under three different curing conditions. The curing conditions simulate the effect of different environmental conditions prevailing in the central and coastal regions of the Arabian Peninsula on the properties of SHCC as a retrofit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…The ductility property of a structural element is an important factor that reveals its reliability. This property can be described as the capability of a structural element to plastically resist loading between its yield to ultimate points [47]. The evaluation of the yield point can be made by graphical and equivalent toughness approaches [48].…”
Section: Ductility Analysismentioning
confidence: 99%
“…The ductility property of a structural element is an important factor that reveals its reliability. This property can be described as the capability of a structural element to plastically resist loading between its yield to ultimate points [47]. The evaluation of the yield point can be made by graphical and equivalent toughness approaches [48].…”
Section: Ductility Analysismentioning
confidence: 99%
“…In this study, it was demonstrated that reinforcement percentage and type influenced failure mode. Recently, Khan et al [ 42 ] investigated the impact of the hot and steam curing regimes on the flexural properties of RC beams retrofitted with a 50 mm-thick SHCC layer in the tension zone. A lower ductility was observed in the strengthened beams under hot and steam curing.…”
Section: Introductionmentioning
confidence: 99%